2018
DOI: 10.7554/elife.32569
|View full text |Cite
|
Sign up to set email alerts
|

Clathrin coat controls synaptic vesicle acidification by blocking vacuolar ATPase activity

Abstract: Newly-formed synaptic vesicles (SVs) are rapidly acidified by vacuolar adenosine triphosphatases (vATPases), generating a proton electrochemical gradient that drives neurotransmitter loading. Clathrin-mediated endocytosis is needed for the formation of new SVs, yet it is unclear when endocytosed vesicles acidify and refill at the synapse. Here, we isolated clathrin-coated vesicles (CCVs) from mouse brain to measure their acidification directly at the single vesicle level. We observed that the ATP-induced acidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
41
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 49 publications
2
41
0
Order By: Relevance
“…The combined use of an optimized purification protocol and the single vesicle assay allows for a highly sensitive, qualitative, and quantitative investigation of the acidification process. This study revealed that the clathrin coat on the endocytosed vesicle blocks the vATPase activity, while the uncoating of the same vesicle releases this inhibition . Therefore, vesicle coating acts as a checkpoint between the retrieval step and acidification/neurotransmitter refilling.…”
Section: Regulation Of the Vatpase Activity During Sv Recyclingmentioning
confidence: 86%
See 4 more Smart Citations
“…The combined use of an optimized purification protocol and the single vesicle assay allows for a highly sensitive, qualitative, and quantitative investigation of the acidification process. This study revealed that the clathrin coat on the endocytosed vesicle blocks the vATPase activity, while the uncoating of the same vesicle releases this inhibition . Therefore, vesicle coating acts as a checkpoint between the retrieval step and acidification/neurotransmitter refilling.…”
Section: Regulation Of the Vatpase Activity During Sv Recyclingmentioning
confidence: 86%
“…In an attempt to address this, Farsi et al (2018) optimized a protocol (adapted from Reference ) to isolate CCVs from mouse brains, and used this sample in a single vesicle assay designed to measure both components of electrochemical gradient, ΔpH and Δψ. The combined use of an optimized purification protocol and the single vesicle assay allows for a highly sensitive, qualitative, and quantitative investigation of the acidification process.…”
Section: Regulation Of the Vatpase Activity During Sv Recyclingmentioning
confidence: 99%
See 3 more Smart Citations